PMP practice questions - Francis, David (Exam cram 2., 2004)
The PMP Practice Questions Exam Cram 2 offers you a solid opportunity to drill and practice for the highly critical professional exam. The book features 500 questions based on the 9 Project Management Processes described in the PMI PMBOK and in our PMP Exam Cram 2. All questions found in the book will also be on the accompanying CD in a test engine powered by MeasureUp. The questions will have full explanations of correct and incorrect answers so you can use this manual to review and brush-up on weak areas. It features relevant Exam Notes to help you score better on the test, plus the ever popular "Cram Sheet" tear card, to use for last-minute cramming. Join the ranks of readers that have chosen Exam Cram 2 as part of their preparation for their certification exams!.